Preparation method of heat-resistant fine enameled round copper wire
Through a multi-step preparation method, combined with specific composite solutions and powders, the performance problems of fine enameled copper wires under high temperature or high voltage conditions are solved, and the high thermal stability and corona resistance are improved, and the application field is broadened.
Patent Information
- Application Number
- CN202411978183.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing fine enameled copper wires are prone to problems such as wire breakage, paint removal, corrosion and aging, low resistance balance rate and inaccurate information transmission under high temperature or high voltage conditions.
A heat-resistant fine enameled round copper wire is prepared by configuring a specific composite solution and powder, and undergoing multi-step stirring, heating, standing, washing and calcining treatment, to form a modified powder and filler powder, and finally mixing it with polyesterimine resin to prepare a paint liquid with high thermal stability and corona resistance.
Improves the thermal stability and corona resistance of enameled copper wire, allowing it to be used at high temperatures or high voltages, extends the life of the product and broadens its application areas.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper wire coatings, and in particular to a method for preparing a heat-resistant fine enameled round copper wire. Background Art
[0002] In recent years, as electronic, electrical, motor, transformer, automobile and other products continue to develop towards miniaturization, ultra-thinness, ultra-miniaturization and high reliability, the demand for fine enameled copper wire has increased rapidly year by year. More and more customers are trying it out, and the application field is also expanding rapidly. Enameled wire usually consists of two parts: conductor and insulation layer. After the bare wire is annealed and softened, it is painted and baked several times. Enameled wire has four major properties: mechanical properties, chemical properties, electrical properties, and thermal properties. However, it is not easy to produce products that meet both the requirements and the requirements of customers. It is affected by factors such as raw material quality, process parameters, production equipment, and environment. Ordinary enameled wire is prone to problems such as broken wire, paint peeling (paint film cracks, cracks), corrosion aging, low resistance balance rate, and information transmission accuracy that does not meet the requirements. Summary of the invention
[0003] To this end, the present invention provides a method for preparing a heat-resistant fine enameled round copper wire, the preparation steps comprising:
[0004] (1) preparing a composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine; preparing a composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene; preparing an ethanol solution of boric acid; mixing the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene with the ethanol solution of boric acid, stirring for more than 30 minutes after mixing, then adding the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine to the mixed solution under stirring, heating to 60±5° C. in a water bath after the addition is completed, stirring at 60±5° C. for more than 20 minutes, then adding ammonia water under stirring, continuing to stir at a constant temperature of 60±5° C. for more than 3 hours after the addition is completed, standing at room temperature for more than 10 hours, separating the solid from the liquid, washing the solid phase with ethanol for more than two times, and then washing with deionized water for more than two times, calcining at 550±10° C. for 60 to 80 minutes, and obtaining a doped powder;
[0005] (2) adding γ-glycidyloxypropyltrimethoxysilane to an aqueous solution of ethanol, stirring for more than 1 hour, then adding the doped powder to the solution under stirring, heating to 80±5° C. in a water bath and stirring for more than 1 hour after the addition is completed, then separating the solid and the liquid, washing the solid phase with ethanol for more than 3 times, and drying to obtain a dried powder; preparing an ethanol solution of N-(4-hydroxyphenyl)maleimide in a reactor, stirring the ethanol solution of N-(4-hydroxyphenyl)maleimide, then adding the dried powder and triphenylphosphine to the solution under stirring, continuing to stir for more than 20 minutes after the addition is completed, then closing the reactor, exhausting the air in the reactor with nitrogen so that the reactor is in a nitrogen protection environment, heating to 130±3° C. and keeping warm for more than 3 hours, air cooling to room temperature after the insulation is completed, opening the reactor, separating the solid and the liquid, washing the solid phase with ethanol for more than 2 times, and then washing with deionized water for more than 2 times, and drying to obtain a modified powder;
[0006] (3) cerium acetate, 2-ethyl-4-methylimidazole and dichloromethane are mixed to form a mixture, the mixture is stirred for more than 50 minutes, and then the modified powder is added to the mixture under stirring. After the addition is completed, stirring is continued for more than 1 hour, and then the mixture is allowed to stand at room temperature for more than 20 hours. After the standing is completed, the solid-liquid separation is carried out, the solid phase is washed with ethanol for more than 2 times, and dried to obtain a filler powder;
[0007] (4) adding the filler powder into xylene and stirring for more than 30 minutes to obtain a dispersion, then adding the dispersion into a polyesterimide resin and stirring for more than 6 hours to obtain a paint solution, coating the paint solution on the outside of the round copper wire, then keeping the temperature at 180±5°C for 10 to 15 minutes, then heating to 250±5°C and keeping the temperature for 15 to 20 minutes, and air cooling to room temperature to obtain the fine enameled round copper wire.
[0008] Furthermore, in the step (1), in the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine, the concentration of hexadecyltrimethylammonium bromide is 3-4 g / 100 mL, the concentration of triethylamine is 0.3-0.4 g / 100 mL, and the solvent is water; in the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene, the concentration of tetraethyl orthosilicate is 10-15 g / 100 mL, the concentration of 1-tetradecene is 1-2 g / 100 mL, and the solvent is ethanol; in the ethanol solution of boric acid, the concentration of boric acid is 0.8-1 g / 100 mL, and the solvent is ethanol.
[0009] Furthermore, in the step (1), the volume ratio of the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene, the ethanol solution of boric acid, the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine, and aqueous ammonia is 10:3-4:8-10:2-4 for the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene: ethanol solution of boric acid: composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine: aqueous ammonia, wherein the mass percentage of the solute in the aqueous ammonia is 10%.
[0010] Furthermore, in the step (2), the volume ratio of γ-glycidyloxypropyltrimethoxysilane added to the ethanol aqueous solution is γ-glycidyloxypropyltrimethoxysilane: ethanol aqueous solution = 1:80-100, wherein the volume percentage of ethanol in the ethanol aqueous solution is 85%-90%; the mass ratio of the doping powder added to the solution is doping powder: solution = 1:50-100.
[0011] Furthermore, in the step (2), in the ethanol solution of N-(4-hydroxyphenyl)maleimide, the concentration of N-(4-hydroxyphenyl)maleimide is 0.6-0.9 g / 100 mL, and the solvent is ethanol; the dried powder and triphenylphosphine are added to the ethanol solution of N-(4-hydroxyphenyl)maleimide in a ratio of dried powder: triphenylphosphine: ethanol solution of N-(4-hydroxyphenyl)maleimide = 1-3 g: 0.2-0.3 g: 100 mL.
[0012] Furthermore, in the step (3), the mass ratio of the cerium acetate, 2-ethyl-4-methylimidazole and dichloromethane is cerium acetate: 2-ethyl-4-methylimidazole: dichloromethane = 1.3-1.8: 1.2-1.6: 100; and the mass ratio of the modified powder added to the mixture is mixture: modified powder = 50:1.
[0013] Furthermore, in the step (4), the mass ratio of the filler powder added to xylene is filler powder:xylene=1:15-20; and the mass percentage of the filler powder in the paint solution is 10%-12%.
[0014] The beneficial effect of the present invention is that the paint film of the enameled round copper wire prepared by the method of the present invention has high thermal stability and corona resistance, so that the enameled copper wire can be used in occasions with high temperature or high voltage load, the durability of the enameled copper wire is improved, and the application field is broadened. The present invention dopes boron while preparing nano silicon oxide powder, and then modifies the group structure on the surface of the powder. Since the boron oxygen bond has a higher bond energy than the silicon oxygen bond, the modified molecule and the matrix powder are more closely combined. In the process of preparing the paint layer, the second phase particle surface macromolecule and the polyester imide resin indirectly improve the bonding force between the polyester imide resin and the reinforcing phase particles. Subsequently, epoxy groups are introduced on the particle surface by γ-glycidyl ether oxypropyl trimethoxy silane, and then N-(4-hydroxyphenyl) maleimide is added for modification, and a phenylimide structure is introduced. On the one hand, the modified structure is conducive to improving the dispersibility of the particles, and on the other hand, due to the high stability of the phenylimide structure, the heat resistance of the paint layer as a whole is improved. Finally, through the modification of cerium acetate and 2-ethyl-4-methylimidazole, a network structure with reinforcing phase particles as nodes is formed during the subsequent curing process of the paint liquid, which improves the overall strength and heat resistance of the paint layer. The stronger the bonding force between the filler particles and the resin matrix, the higher the energy required to destroy this structure, and the material's ability to capture carriers is also higher. The captured carriers form a reverse electric field that can weaken the intensity of the external electric field electron bombarding the paint layer, and the corona resistance is stronger. At the same time, the better the dispersion of the filler particles, the more uniform the distribution of the carrier trap density, and the more uniform the reverse electric field strength formed, which is less likely to form a concentrated intensity that causes local damage to the paint layer and causes the overall paint layer to break through, and can also improve the corona resistance of the paint layer. DETAILED DESCRIPTION
[0015] The present invention will be further described below in conjunction with the embodiments.
[0016] Example 1
[0017] A method for preparing a heat-resistant fine enameled round copper wire, the preparation steps comprising:
[0018] (1) preparing a composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine; preparing a composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene; preparing an ethanol solution of boric acid; in the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine, the concentration of hexadecyltrimethylammonium bromide is 3 g / 100 mL, the concentration of triethylamine is 0.3 g / 100 mL, and the solvent is water; in the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene, the concentration of tetraethyl orthosilicate is 10 g / 100 mL, the concentration of 1-tetradecene is 1 g / 100 mL, and the solvent is ethanol; in the ethanol solution of boric acid, the concentration of boric acid is 0.8 g / 100 mL, and the solvent is ethanol; the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene and the ethanol solution of boric acid are mixed, stirred for 30 minutes after mixing, and then stirred under stirring. The composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine is added to the mixed solution, and after the addition is completed, the mixture is heated to 60° C. in a water bath, and stirred at 60° C. for 20 minutes, and then ammonia water is added under stirring, and the volume ratio of the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene, the ethanol solution of boric acid, the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine, and ammonia water is 10:3:8:2 for the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene: the ethanol solution of boric acid: the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine: ammonia water, wherein the mass percentage of the solute in the ammonia water is 10%; after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 3 hours, and then allowed to stand at room temperature for 10 hours, solid-liquid separation is performed, the solid phase is washed twice with ethanol, and then washed twice with deionized water, and calcined at 550° C. for 60 minutes to obtain a doped powder;
[0019] (2) adding γ-glycidyloxypropyltrimethoxysilane to an aqueous solution of ethanol, wherein the volume ratio of the γ-glycidyloxypropyltrimethoxysilane to the aqueous solution of ethanol is γ-glycidyloxypropyltrimethoxysilane: the aqueous solution of ethanol = 1:80, wherein the volume percentage of ethanol in the aqueous solution of ethanol is 85%; stirring for 1 hour, and then adding the doping powder to the solution under stirring, wherein the mass ratio of the doping powder to the solution is doping powder: solution = 1:50; after the addition is completed, heating to 80° C. in a water bath and stirring for 1 hour, and then separating the solid and the liquid, washing the solid phase with ethanol for 3 times, and drying at 80° C. for 40 minutes to obtain a dried powder; preparing an ethanol solution of N-(4-hydroxyphenyl)maleimide in a reactor, wherein the ethanol solution of N-(4-hydroxyphenyl)maleimide The concentration of N-(4-hydroxyphenyl)maleimide is 0.6g / 100mL, and the solvent is ethanol; the ethanol solution of N-(4-hydroxyphenyl)maleimide is stirred, and then the dried powder and triphenylphosphine are added to the solution under stirring, and the amount ratio of the dried powder and triphenylphosphine added to the ethanol solution of N-(4-hydroxyphenyl)maleimide is dried powder: triphenylphosphine: ethanol solution of N-(4-hydroxyphenyl)maleimide = 1g: 0.2g: 100mL; after the addition is completed, stirring is continued for 20min, and then the reactor is closed, the air in the reactor is discharged with nitrogen so that the reactor is in a nitrogen protection environment, heated to 130°C and kept warm for 3h, after the insulation is completed, air-cooled to room temperature, the reactor is opened, solid-liquid separation is carried out, the solid phase is washed twice with ethanol, and then washed twice with deionized water, and dried at 80°C for 40min to obtain a modified powder;
[0020] (3) Cerium acetate, 2-ethyl-4-methylimidazole and dichloromethane are mixed to form a mixture, wherein the mass ratio of the cerium acetate, 2-ethyl-4-methylimidazole and dichloromethane is cerium acetate: 2-ethyl-4-methylimidazole: dichloromethane = 1.3:1.2:100; the mixture is stirred for 50 minutes, and then the modified powder is added to the mixture under stirring, and the mass ratio of the modified powder added to the mixture is mixture: modified powder = 50:1; after the addition is completed, the stirring is continued for 1 hour, and then the mixture is allowed to stand at room temperature for 20 hours. After the standing is completed, the solid-liquid separation is performed, the solid phase is washed twice with ethanol, and dried at 80° C. for 40 minutes to obtain a filler powder;
[0021] (4) Add the filler powder to xylene, the mass ratio of the filler powder to xylene is filler powder: xylene = 1:15; stir for 30 minutes to obtain a dispersion, then add the dispersion to a polyester imide resin and stir for 6 hours to obtain a paint solution, the mass percentage of the filler powder in the paint solution is 10%; apply the paint solution on the outside of the round copper wire and the surface of the aluminum foil (as a corona resistance test sample substrate), then keep the temperature at 180°C for 10 minutes, then increase the temperature to 250°C and keep the temperature for 15 minutes, and air cool to room temperature to obtain the enameled round copper wire and the corona resistance test sample described in this embodiment, the paint layer thickness of both is 25 μm.
[0022] Example 2
[0023] A method for preparing a heat-resistant fine enameled round copper wire, the preparation steps comprising:
[0024] (1) preparing a composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine; preparing a composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene; preparing an ethanol solution of boric acid; in the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine, the concentration of hexadecyltrimethylammonium bromide is 3 g / 100 mL, the concentration of triethylamine is 0.3 g / 100 mL, and the solvent is water; in the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene, the concentration of tetraethyl orthosilicate is 12 g / 100 mL, the concentration of 1-tetradecene is 1 g / 100 mL, and the solvent is ethanol; in the ethanol solution of boric acid, the concentration of boric acid is 0.9 g / 100 mL, and the solvent is ethanol; the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene and the ethanol solution of boric acid are mixed, stirred for 30 minutes after mixing, and then stirred under stirring. The composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine is added to the mixed solution, and after the addition is completed, the mixture is heated to 60° C. in a water bath, and stirred at 60° C. for 20 minutes, and then ammonia water is added under stirring, and the volume ratio of the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene, the ethanol solution of boric acid, the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine, and ammonia water is 10:3:9:3 for the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene: the ethanol solution of boric acid: the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine: ammonia water, wherein the mass percentage of the solute in the ammonia water is 10%; after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 3 hours, and then allowed to stand at room temperature for 10 hours, solid-liquid separation is performed, the solid phase is washed twice with ethanol, and then washed twice with deionized water, and calcined at 550° C. for 60 minutes to obtain a doped powder;
[0025] (2) adding γ-glycidyloxypropyltrimethoxysilane to an aqueous solution of ethanol, wherein the volume ratio of the γ-glycidyloxypropyltrimethoxysilane to the aqueous solution of ethanol is γ-glycidyloxypropyltrimethoxysilane: the aqueous solution of ethanol = 1:90, wherein the volume percentage of ethanol in the aqueous solution of ethanol is 85%; stirring for 1 hour, and then adding the doping powder to the solution under stirring, wherein the mass ratio of the doping powder to the solution is doping powder: solution = 1:50; after the addition is completed, heating to 80° C. in a water bath and stirring for 1 hour, and then separating the solid and the liquid, washing the solid phase with ethanol for 3 times, and drying at 80° C. for 40 minutes to obtain a dried powder; preparing an ethanol solution of N-(4-hydroxyphenyl)maleimide in a reactor, wherein the ethanol solution of N-(4-hydroxyphenyl)maleimide The concentration of N-(4-hydroxyphenyl)maleimide is 0.7g / 100mL, and the solvent is ethanol; the ethanol solution of N-(4-hydroxyphenyl)maleimide is stirred, and then the dried powder and triphenylphosphine are added to the solution under stirring, and the amount ratio of the dried powder and triphenylphosphine added to the ethanol solution of N-(4-hydroxyphenyl)maleimide is dried powder: triphenylphosphine: ethanol solution of N-(4-hydroxyphenyl)maleimide = 2g: 0.2g: 100mL; after the addition is completed, stirring is continued for 20min, and then the reactor is closed, the air in the reactor is discharged with nitrogen so that the reactor is in a nitrogen protection environment, heated to 130°C and kept warm for 3h, after the insulation is completed, air-cooled to room temperature, the reactor is opened, solid-liquid separation, the solid phase is washed twice with ethanol, and then washed twice with deionized water, and dried at 80°C for 40min to obtain a modified powder;
[0026] (3) Cerium acetate, 2-ethyl-4-methylimidazole and dichloromethane are mixed to form a mixture, wherein the mass ratio of the cerium acetate, 2-ethyl-4-methylimidazole and dichloromethane is cerium acetate: 2-ethyl-4-methylimidazole: dichloromethane = 1.5:1.4:100; the mixture is stirred for 50 minutes, and then the modified powder is added to the mixture under stirring, and the mass ratio of the modified powder added to the mixture is mixture: modified powder = 50:1; after the addition is completed, stirring is continued for 1 hour, and then the mixture is allowed to stand at room temperature for 20 hours. After the standing is completed, solid-liquid separation is performed, the solid phase is washed twice with ethanol, and dried at 80° C. for 40 minutes to obtain a filler powder;
[0027] (4) Add the filler powder to xylene, the mass ratio of the filler powder to xylene is filler powder: xylene = 1:15; stir for 30 minutes to obtain a dispersion, then add the dispersion to a polyester imide resin and stir for 6 hours to obtain a paint solution, the mass percentage of the filler powder in the paint solution is 11%; apply the paint solution on the outside of the round copper wire and the surface of the aluminum foil (as a corona resistance test sample substrate), then keep the temperature at 180°C for 10 minutes, then increase the temperature to 250°C and keep the temperature for 15 minutes, and air cool to room temperature to obtain the enameled round copper wire and the corona resistance test sample described in this embodiment, the paint layer thickness of both is 25 μm.
[0028] Example 3
[0029] A method for preparing a heat-resistant fine enameled round copper wire, the preparation steps comprising:
[0030] (1) preparing a composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine; preparing a composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene; preparing an ethanol solution of boric acid; in the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine, the concentration of hexadecyltrimethylammonium bromide is 4 g / 100 mL, the concentration of triethylamine is 0.4 g / 100 mL, and the solvent is water; in the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene, the concentration of tetraethyl orthosilicate is 14 g / 100 mL, the concentration of 1-tetradecene is 2 g / 100 mL, and the solvent is ethanol; in the ethanol solution of boric acid, the concentration of boric acid is 0.9 g / 100 mL, and the solvent is ethanol; the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene and the ethanol solution of boric acid are mixed, stirred for 30 minutes after mixing, and then stirred under stirring. The composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine is added to the mixed solution, and after the addition is completed, the mixture is heated to 60° C. in a water bath, and stirred at 60° C. for 20 minutes, and then ammonia water is added under stirring, and the mixed volume ratio of the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene, the ethanol solution of boric acid, the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine, and ammonia water is 10:4:9:3 for the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene: the ethanol solution of boric acid: the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine: ammonia water, wherein the mass percentage of the solute in the ammonia water is 10%; after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 3 hours, and then allowed to stand at room temperature for 10 hours, solid-liquid separation is performed, the solid phase is washed twice with ethanol, and then washed twice with deionized water, and calcined at 550° C. for 60 minutes to obtain a doped powder;
[0031] (2) adding γ-glycidyloxypropyltrimethoxysilane to an aqueous solution of ethanol, wherein the volume ratio of the γ-glycidyloxypropyltrimethoxysilane to the aqueous solution of ethanol is γ-glycidyloxypropyltrimethoxysilane: the aqueous solution of ethanol = 1:80, wherein the volume percentage of ethanol in the aqueous solution of ethanol is 90%; stirring for 1 hour, and then adding the doping powder to the solution under stirring, wherein the mass ratio of the doping powder to the solution is doping powder: solution = 1:50; after the addition is completed, heating to 80° C. in a water bath and stirring for 1 hour, and then separating the solid and the liquid, washing the solid phase with ethanol for 3 times, and drying at 80° C. for 40 minutes to obtain a dried powder; preparing an ethanol solution of N-(4-hydroxyphenyl)maleimide in a reactor, wherein the ethanol solution of N-(4-hydroxyphenyl)maleimide The concentration of N-(4-hydroxyphenyl)maleimide is 0.8g / 100mL, and the solvent is ethanol; the ethanol solution of N-(4-hydroxyphenyl)maleimide is stirred, and then the dried powder and triphenylphosphine are added to the solution under stirring, and the amount ratio of the dried powder and triphenylphosphine added to the ethanol solution of N-(4-hydroxyphenyl)maleimide is dried powder: triphenylphosphine: ethanol solution of N-(4-hydroxyphenyl)maleimide = 2g: 0.3g: 100mL; after the addition is completed, stirring is continued for 20min, and then the reactor is closed, the air in the reactor is discharged with nitrogen so that the reactor is in a nitrogen protection environment, heated to 130°C and kept warm for 3h, after the insulation is completed, air-cooled to room temperature, the reactor is opened, solid-liquid separation is carried out, the solid phase is washed twice with ethanol, and then washed twice with deionized water, and dried at 80°C for 40min to obtain a modified powder;
[0032] (3) Cerium acetate, 2-ethyl-4-methylimidazole and dichloromethane are mixed to form a mixture, wherein the mass ratio of the cerium acetate, 2-ethyl-4-methylimidazole and dichloromethane is cerium acetate: 2-ethyl-4-methylimidazole: dichloromethane = 1.6:1.4:100; the mixture is stirred for 50 minutes, and then the modified powder is added to the mixture under stirring, and the mass ratio of the modified powder added to the mixture is mixture: modified powder = 50:1; after the addition is completed, the stirring is continued for 1 hour, and then the mixture is allowed to stand at room temperature for 20 hours. After the standing is completed, the solid-liquid separation is performed, the solid phase is washed twice with ethanol, and dried at 80° C. for 40 minutes to obtain a filler powder;
[0033] (4) Add the filler powder to xylene, the mass ratio of the filler powder to xylene is filler powder: xylene = 1:15; stir for 30 minutes to obtain a dispersion, then add the dispersion to a polyester imide resin and stir for 6 hours to obtain a paint solution, the mass percentage of the filler powder in the paint solution is 11%; apply the paint solution on the outside of the round copper wire and the surface of the aluminum foil (as a corona resistance test sample substrate), then keep the temperature at 180°C for 10 minutes, then increase the temperature to 250°C and keep the temperature for 15 minutes, and air cool to room temperature to obtain the enameled round copper wire and the corona resistance test sample described in this embodiment, the paint layer thickness of both is 25 μm.
[0034] Example 4
[0035] A method for preparing a heat-resistant fine enameled round copper wire, the preparation steps comprising:
[0036] (1) preparing a composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine; preparing a composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene; preparing an ethanol solution of boric acid; in the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine, the concentration of hexadecyltrimethylammonium bromide is 4 g / 100 mL, the concentration of triethylamine is 0.4 g / 100 mL, and the solvent is water; in the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene, the concentration of tetraethyl orthosilicate is 15 g / 100 mL, the concentration of 1-tetradecene is 2 g / 100 mL, and the solvent is ethanol; in the ethanol solution of boric acid, the concentration of boric acid is 1 g / 100 mL, and the solvent is ethanol; the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene and the ethanol solution of boric acid are mixed, stirred for 30 minutes after mixing, and then added to the mixture under stirring; The composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine is added to the mixed liquid, and after the addition is completed, the mixture is heated to 60° C. in a water bath, stirred at 60° C. for 20 min, and then ammonia water is added under stirring, and the volume ratio of the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene, the ethanol solution of boric acid, the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine, and ammonia water is 10:4:10:4 for the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene: the ethanol solution of boric acid: the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine: ammonia water, wherein the mass percentage of the solute in the ammonia water is 10%; after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 3 h, and then allowed to stand at room temperature for 10 h, solid-liquid separation is performed, the solid phase is washed twice with ethanol, and then washed twice with deionized water, and calcined at 550° C. for 60 min to obtain a doped powder;
[0037] (2) adding γ-glycidyloxypropyltrimethoxysilane to an aqueous solution of ethanol, wherein the volume ratio of the γ-glycidyloxypropyltrimethoxysilane to the aqueous solution of ethanol is γ-glycidyloxypropyltrimethoxysilane: the aqueous solution of ethanol = 1:80, wherein the volume percentage of ethanol in the aqueous solution of ethanol is 90%; stirring for 1 hour, and then adding the doping powder to the solution under stirring, wherein the mass ratio of the doping powder to the solution is doping powder: solution = 1:50; after the addition is completed, heating to 80° C. in a water bath and stirring for 1 hour, and then separating the solid and the liquid, washing the solid phase with ethanol for 3 times, and drying at 80° C. for 40 minutes to obtain a dried powder; preparing an ethanol solution of N-(4-hydroxyphenyl)maleimide in a reactor, wherein the ethanol solution of N-(4-hydroxyphenyl)maleimide The concentration of N-(4-hydroxyphenyl)maleimide is 0.9g / 100mL, and the solvent is ethanol; the ethanol solution of N-(4-hydroxyphenyl)maleimide is stirred, and then the dried powder and triphenylphosphine are added to the solution under stirring, and the amount ratio of the dried powder and triphenylphosphine added to the ethanol solution of N-(4-hydroxyphenyl)maleimide is dried powder: triphenylphosphine: ethanol solution of N-(4-hydroxyphenyl)maleimide = 3g: 0.3g: 100mL; after the addition is completed, stirring is continued for 20min, and then the reactor is closed, the air in the reactor is discharged with nitrogen so that the reactor is in a nitrogen protection environment, heated to 130°C and kept warm for 3h, after the insulation is completed, air-cooled to room temperature, the reactor is opened, solid-liquid separation is carried out, the solid phase is washed twice with ethanol, and then washed twice with deionized water, and dried at 80°C for 40min to obtain a modified powder;
[0038] (3) Cerium acetate, 2-ethyl-4-methylimidazole and dichloromethane are mixed to form a mixture, wherein the mass ratio of the cerium acetate, 2-ethyl-4-methylimidazole and dichloromethane is cerium acetate: 2-ethyl-4-methylimidazole: dichloromethane = 1.8:1.6:100; the mixture is stirred for 50 minutes, and then the modified powder is added to the mixture under stirring, and the mass ratio of the modified powder added to the mixture is mixture: modified powder = 50:1; after the addition is completed, the stirring is continued for 1 hour, and then the mixture is allowed to stand at room temperature for 20 hours. After the standing is completed, the solid-liquid separation is performed, the solid phase is washed twice with ethanol, and dried at 80° C. for 40 minutes to obtain a filler powder;
[0039] (4) Add the filler powder to xylene, the mass ratio of the filler powder to xylene is filler powder: xylene = 1:15; stir for 30 minutes to obtain a dispersion, then add the dispersion to a polyester imide resin and stir for 6 hours to obtain a paint solution, the mass percentage of the filler powder in the paint solution is 12%; apply the paint solution on the outside of the round copper wire and the surface of the aluminum foil (as a corona resistance test sample substrate), then keep the temperature at 180°C for 10 minutes, then increase the temperature to 250°C and keep the temperature for 15 minutes, and air cool to room temperature to obtain the enameled round copper wire and the corona resistance test sample described in this embodiment, the paint layer thickness of both is 25 μm.
[0040] Comparative Example 1
[0041] A comparative method for preparing an enameled round copper wire comprises the following steps:
[0042] (1) preparing a composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine; preparing a composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene; in the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine, the concentration of hexadecyltrimethylammonium bromide is 3 g / 100 mL, the concentration of triethylamine is 0.3 g / 100 mL, and the solvent is water; in the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene, the concentration of tetraethyl orthosilicate is 12 g / 100 mL, the concentration of 1-tetradecene is 1 g / 100 mL, and the solvent is ethanol; stirring the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene for 30 minutes, and then adding the composite ethanol solution of hexadecyltrimethylammonium bromide and triethylamine under stirring; The aqueous solution is heated to 60° C. in a water bath after the addition is completed, and stirred at 60° C. for 20 min, and then ammonia water is added under stirring, and the mixed volume ratio of the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene and the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine and ammonia water is 10:9:3 for the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene: the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine: ammonia water, wherein the mass percentage of the solute in the ammonia water is 10%; after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 3 h, and then allowed to stand at room temperature for 10 h, solid-liquid separation is performed, the solid phase is washed twice with ethanol, and then washed twice with deionized water, and calcined at 550° C. for 60 min to obtain the doped powder of this comparative example;
[0043] (2) adding γ-glycidyloxypropyltrimethoxysilane to an aqueous solution of ethanol, wherein the volume ratio of the γ-glycidyloxypropyltrimethoxysilane to the aqueous solution of ethanol is γ-glycidyloxypropyltrimethoxysilane: the aqueous solution of ethanol = 1:90, wherein the volume percentage of ethanol in the aqueous solution of ethanol is 85%; stirring for 1 hour, and then adding the doping powder to the solution under stirring, wherein the mass ratio of the doping powder to the solution is doping powder: solution = 1:50; after the addition is completed, heating to 80° C. in a water bath and stirring for 1 hour, and then separating the solid and the liquid, washing the solid phase with ethanol for 3 times, and drying at 80° C. for 40 minutes to obtain a dried powder; preparing an ethanol solution of N-(4-hydroxyphenyl)maleimide in a reactor, wherein the ethanol solution of N-(4-hydroxyphenyl)maleimide The concentration of N-(4-hydroxyphenyl)maleimide is 0.7g / 100mL, and the solvent is ethanol; the ethanol solution of N-(4-hydroxyphenyl)maleimide is stirred, and then the dried powder and triphenylphosphine are added to the solution under stirring, and the amount ratio of the dried powder and triphenylphosphine added to the ethanol solution of N-(4-hydroxyphenyl)maleimide is dried powder: triphenylphosphine: ethanol solution of N-(4-hydroxyphenyl)maleimide = 2g: 0.2g: 100mL; after the addition is completed, stirring is continued for 20min, and then the reactor is closed, the air in the reactor is discharged with nitrogen so that the reactor is in a nitrogen protection environment, heated to 130°C and kept warm for 3h, after the insulation is completed, air-cooled to room temperature, the reactor is opened, solid-liquid separation, the solid phase is washed twice with ethanol, and then washed twice with deionized water, and dried at 80°C for 40min to obtain a modified powder;
[0044] (3) Cerium acetate, 2-ethyl-4-methylimidazole and dichloromethane are mixed to form a mixture, wherein the mass ratio of the cerium acetate, 2-ethyl-4-methylimidazole and dichloromethane is cerium acetate: 2-ethyl-4-methylimidazole: dichloromethane = 1.5:1.4:100; the mixture is stirred for 50 minutes, and then the modified powder is added to the mixture under stirring, and the mass ratio of the modified powder added to the mixture is mixture: modified powder = 50:1; after the addition is completed, stirring is continued for 1 hour, and then the mixture is allowed to stand at room temperature for 20 hours. After the standing is completed, solid-liquid separation is performed, the solid phase is washed twice with ethanol, and dried at 80° C. for 40 minutes to obtain a filler powder;
[0045] (4) Add the filler powder to xylene, the mass ratio of the filler powder to xylene is filler powder: xylene = 1:15; stir for 30 minutes to obtain a dispersion, then add the dispersion to the polyesterimide resin and stir for 6 hours to obtain the paint solution of this comparative example, the mass percentage of the filler powder in the paint solution is 11%; apply the paint solution on the outside of the round copper wire and the surface of the aluminum foil (as the substrate of the corona resistance test sample), then keep the temperature at 180°C for 10 minutes, then increase the temperature to 250°C and keep the temperature for 15 minutes, and air cool to room temperature to obtain the enameled round copper wire and the corona resistance test sample of this comparative example, the paint layer thickness of both is 25 μm.
[0046] Comparative Example 2
[0047] A comparative method for preparing an enameled round copper wire comprises the following steps:
[0048] (1) preparing a composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine; preparing a composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene; preparing an ethanol solution of boric acid; in the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine, the concentration of hexadecyltrimethylammonium bromide is 3 g / 100 mL, the concentration of triethylamine is 0.3 g / 100 mL, and the solvent is water; in the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene, the concentration of tetraethyl orthosilicate is 12 g / 100 mL, the concentration of 1-tetradecene is 1 g / 100 mL, and the solvent is ethanol; in the ethanol solution of boric acid, the concentration of boric acid is 0.9 g / 100 mL, and the solvent is ethanol; the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene and the ethanol solution of boric acid are mixed, stirred for 30 minutes after mixing, and then stirred under stirring. The composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine is added to the mixed solution, and after the addition is completed, the mixture is heated to 60° C. in a water bath, and stirred at 60° C. for 20 minutes, and then ammonia water is added under stirring, and the volume ratio of the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene, the ethanol solution of boric acid, the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine, and ammonia water is 10:3:9:3 for the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene: the ethanol solution of boric acid: the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine: ammonia water, wherein the mass percentage of the solute in the ammonia water is 10%; after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 3 hours, and then allowed to stand at room temperature for 10 hours, solid-liquid separation is performed, the solid phase is washed twice with ethanol, and then washed twice with deionized water, and calcined at 550° C. for 60 minutes to obtain a doped powder;
[0049] (2) adding γ-glycidyloxypropyltrimethoxysilane to an aqueous solution of ethanol, wherein the volume ratio of the γ-glycidyloxypropyltrimethoxysilane to the aqueous solution of ethanol is γ-glycidyloxypropyltrimethoxysilane: ethanol aqueous solution = 1:90, wherein the volume percentage of ethanol in the aqueous solution of ethanol is 85%; stirring for 1 hour, and then adding the doping powder to the solution under stirring, and the mass ratio of the doping powder to the solution is doping powder: solution = 1:50; after the addition is completed, heating to 80° C. in a water bath and stirring for 1 hour, and then separating the solid and liquid, washing the solid phase with ethanol 3 times, and drying at 80° C. for 40 minutes to obtain the modified powder of this comparative example;
[0050] (3) Cerium acetate, 2-ethyl-4-methylimidazole and dichloromethane are mixed to form a mixture, wherein the mass ratio of the cerium acetate, 2-ethyl-4-methylimidazole and dichloromethane is cerium acetate: 2-ethyl-4-methylimidazole: dichloromethane = 1.5:1.4:100; the mixture is stirred for 50 minutes, and then the modified powder is added to the mixture under stirring, and the mass ratio of the modified powder added to the mixture is mixture: modified powder = 50:1; after the addition is completed, stirring is continued for 1 hour, and then the mixture is allowed to stand at room temperature for 20 hours. After the standing is completed, solid-liquid separation is performed, the solid phase is washed twice with ethanol, and dried at 80° C. for 40 minutes to obtain a filler powder;
[0051] (4) Add the filler powder to xylene, the mass ratio of the filler powder to xylene is filler powder: xylene = 1:15; stir for 30 minutes to obtain a dispersion, then add the dispersion to the polyesterimide resin and stir for 6 hours to obtain the paint solution of this comparative example, the mass percentage of the filler powder in the paint solution is 11%; apply the paint solution on the outside of the round copper wire and the surface of the aluminum foil (as the substrate of the corona resistance test sample), then keep the temperature at 180°C for 10 minutes, then increase the temperature to 250°C and keep the temperature for 15 minutes, and air cool to room temperature to obtain the enameled round copper wire and the corona resistance test sample of this comparative example, the paint layer thickness of both is 25 μm.
[0052] Comparative Example 3
[0053] A comparative method for preparing an enameled round copper wire comprises the following steps:
[0054] (1) preparing a composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine; preparing a composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene; preparing an ethanol solution of boric acid; in the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine, the concentration of hexadecyltrimethylammonium bromide is 3 g / 100 mL, the concentration of triethylamine is 0.3 g / 100 mL, and the solvent is water; in the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene, the concentration of tetraethyl orthosilicate is 12 g / 100 mL, the concentration of 1-tetradecene is 1 g / 100 mL, and the solvent is ethanol; in the ethanol solution of boric acid, the concentration of boric acid is 0.9 g / 100 mL, and the solvent is ethanol; the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene and the ethanol solution of boric acid are mixed, stirred for 30 minutes after mixing, and then stirred under stirring. The composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine is added to the mixed solution, and after the addition is completed, the mixture is heated to 60° C. in a water bath, and stirred at 60° C. for 20 minutes, and then ammonia water is added under stirring, and the volume ratio of the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene, the ethanol solution of boric acid, the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine, and ammonia water is 10:3:9:3 for the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene: the ethanol solution of boric acid: the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine: ammonia water, wherein the mass percentage of the solute in the ammonia water is 10%; after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 3 hours, and then allowed to stand at room temperature for 10 hours, solid-liquid separation is performed, the solid phase is washed twice with ethanol, and then washed twice with deionized water, and calcined at 550° C. for 60 minutes to obtain a doped powder;
[0055] (2) adding γ-glycidyloxypropyltrimethoxysilane to an aqueous solution of ethanol, wherein the volume ratio of the γ-glycidyloxypropyltrimethoxysilane to the aqueous solution of ethanol is γ-glycidyloxypropyltrimethoxysilane: the aqueous solution of ethanol = 1:90, wherein the volume percentage of ethanol in the aqueous solution of ethanol is 85%; stirring for 1 hour, and then adding the doping powder to the solution under stirring, wherein the mass ratio of the doping powder to the solution is doping powder: solution = 1:50; after the addition is completed, heating to 80° C. in a water bath and stirring for 1 hour, and then separating the solid and the liquid, washing the solid phase with ethanol for 3 times, and drying at 80° C. for 40 minutes to obtain a dried powder; preparing an ethanol solution of N-(4-hydroxyphenyl)maleimide in a reactor, wherein the ethanol solution of N-(4-hydroxyphenyl)maleimide The concentration of the amine is 0.7g / 100mL, and the solvent is ethanol; the ethanol solution of N-(4-hydroxyphenyl)maleimide is stirred, and then the dried powder and triphenylphosphine are added to the solution under stirring, and the amount ratio of the dried powder and triphenylphosphine added to the ethanol solution of N-(4-hydroxyphenyl)maleimide is dried powder: triphenylphosphine: ethanol solution of N-(4-hydroxyphenyl)maleimide = 2g: 0.2g: 100mL; after the addition is completed, the stirring is continued for 20min, and then the reactor is closed, the air in the reactor is discharged with nitrogen so that the reactor is in a nitrogen protection environment, heated to 130°C and kept warm for 3h, after the insulation is completed, air-cooled to room temperature, the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed twice with ethanol, and then washed twice with deionized water, and dried at 80°C for 40min to obtain a modified powder as a filler powder of this comparative example;
[0056] (3) Add the filler powder to xylene, the mass ratio of the filler powder to xylene is filler powder: xylene = 1:15; stir for 30 minutes to obtain a dispersion, then add the dispersion to the polyesterimide resin and stir for 6 hours to obtain the paint solution of this comparative example, the mass percentage of the filler powder in the paint solution is 11%; apply the paint solution on the outside of the round copper wire and the surface of the aluminum foil (as the substrate of the corona resistance test sample), then keep the temperature at 180°C for 10 minutes, then increase the temperature to 250°C and keep the temperature for 15 minutes, and air cool to room temperature to obtain the enameled round copper wire and the corona resistance test sample of this comparative example, the paint layer thickness of both is 25 μm.
[0057] Example 5
[0058] The thermal stability of the paint layer prepared by the methods described in the above embodiments and comparative examples was tested by a thermogravimetric analyzer, the heating rate was set to 10°C / min, and the temperature value corresponding to the thermal weight loss of 5% was obtained, and the results are shown in Table 1. The corona resistance test specimens prepared by the methods described in the above embodiments and comparative examples were tested for corona resistance, the test electric field strength was 60kV / mm, the frequency was 50Hz, the test temperature was 155°C, the air humidity was maintained between 35% and 40%, and the air corona discharge was performed above the paint film on the surface of the specimen during the test, and the time for the paint film to break through was recorded, and the results are shown in Table 1.
[0059] As shown in Table 1, the enameled round copper wire paint film prepared by the method of the present invention has high thermal stability and corona resistance, so that the enameled copper wire can be used in occasions with high temperature or high voltage load, which improves the durability of the enameled copper wire and broadens the application field. The present invention dopes boron while preparing nano silicon oxide powder, and then modifies the group structure on the surface of the powder. Since the boron oxygen bond has a higher bond energy than the silicon oxygen bond, the modified molecule and the matrix powder are more closely combined. In the process of preparing the paint layer, the second phase particle surface macromolecule and the polyester imide resin indirectly improve the bonding force between the polyester imide resin and the reinforcing phase particles. Subsequently, an epoxy group is introduced on the particle surface by γ-glycidyl ether oxypropyl trimethoxy silane, and then N-(4-hydroxyphenyl) maleimide is added for modification, and a phenylimide structure is introduced. On the one hand, the modified structure is conducive to improving the dispersibility of the particles, and on the other hand, due to the high stability of the phenylimide structure, the heat resistance of the paint layer as a whole is improved. Finally, through the modification of cerium acetate and 2-ethyl-4-methylimidazole, a network structure with reinforcing phase particles as nodes is formed during the subsequent curing process of the paint liquid, which improves the overall strength and heat resistance of the paint layer. The stronger the bonding force between the filler particles and the resin matrix, the higher the energy required to destroy this structure, and the material's ability to capture carriers is also higher. The captured carriers form a reverse electric field that can weaken the intensity of the external electric field electron bombarding the paint layer, and the corona resistance is stronger. At the same time, the better the dispersion of the filler particles, the more uniform the distribution of the carrier trap density, and the more uniform the reverse electric field strength formed, which is less likely to form a concentrated intensity that causes local damage to the paint layer and causes the overall paint layer to break through, and can also improve the corona resistance of the paint layer.
[0060] Table 1
[0061] Experimental Group Thermal weight loss 5% temperature (℃) Corona resistance time Example 1 423 18h23min Example 2 430 18h37min Example 3 428 18h35min Example 4 425 18h30min Comparative Example 1 419 17h18min Comparative Example 2 416 16h51min Comparative Example 3 412 16h09min
[0062] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A method for preparing a heat-resistant fine enameled round copper wire, characterized in that: The preparation steps include: (1) preparing a composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine; preparing a composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene; preparing an ethanol solution of boric acid; mixing the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene with the ethanol solution of boric acid, stirring for more than 30 minutes after mixing, then adding the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine to the mixed solution under stirring, heating to 60±5° C. in a water bath after the addition is completed, stirring at 60±5° C. for more than 20 minutes, then adding ammonia water under stirring, continuing to stir at a constant temperature of 60±5° C. for more than 3 hours after the addition is completed, standing at room temperature for more than 10 hours, separating the solid from the liquid, washing the solid phase with ethanol for more than two times, and then washing with deionized water for more than two times, calcining at 550±10° C. for 60 to 80 minutes, and obtaining a doped powder; (2) adding γ-glycidyloxypropyltrimethoxysilane to an aqueous solution of ethanol, stirring for more than 1 hour, then adding the doped powder to the solution under stirring, heating to 80±5° C. in a water bath and stirring for more than 1 hour after the addition is completed, then separating the solid and the liquid, washing the solid phase with ethanol for more than 3 times, and drying to obtain a dried powder; preparing an ethanol solution of N-(4-hydroxyphenyl)maleimide in a reactor, stirring the ethanol solution of N-(4-hydroxyphenyl)maleimide, then adding the dried powder and triphenylphosphine to the solution under stirring, continuing to stir for more than 20 minutes after the addition is completed, then closing the reactor, exhausting the air in the reactor with nitrogen so that the reactor is in a nitrogen protection environment, heating to 130±3° C. and keeping warm for more than 3 hours, air cooling to room temperature after the insulation is completed, opening the reactor, separating the solid and the liquid, washing the solid phase with ethanol for more than 2 times, and then washing with deionized water for more than 2 times, and drying to obtain a modified powder; (3) cerium acetate, 2-ethyl-4-methylimidazole and dichloromethane are mixed to form a mixture, the mixture is stirred for more than 50 minutes, and then the modified powder is added to the mixture under stirring. After the addition is completed, stirring is continued for more than 1 hour, and then the mixture is allowed to stand at room temperature for more than 20 hours. After the standing is completed, the solid-liquid separation is carried out, the solid phase is washed with ethanol for more than 2 times, and dried to obtain a filler powder; (4) adding the filler powder into xylene and stirring for more than 30 minutes to obtain a dispersion, then adding the dispersion into a polyesterimide resin and stirring for more than 6 hours to obtain a paint solution, coating the paint solution on the outside of the round copper wire, then keeping the temperature at 180±5°C for 10 to 15 minutes, then heating to 250±5°C and keeping the temperature for 15 to 20 minutes, and air cooling to room temperature to obtain the fine enameled round copper wire.
2. The method for preparing a heat-resistant fine enameled round copper wire according to claim 1, characterized in that: In the step (1), in the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine, the concentration of hexadecyltrimethylammonium bromide is 3-4 g / 100 mL, the concentration of triethylamine is 0.3-0.4 g / 100 mL, and the solvent is water; in the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene, the concentration of tetraethyl orthosilicate is 10-15 g / 100 mL, the concentration of 1-tetradecene is 1-2 g / 100 mL, and the solvent is ethanol; in the ethanol solution of boric acid, the concentration of boric acid is 0.8-1 g / 100 mL, and the solvent is ethanol.
3. The method for preparing a heat-resistant fine enameled round copper wire according to claim 2, characterized in that: In the step (1), the volume ratio of the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene, the ethanol solution of boric acid, the composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine, and aqueous ammonia is 10:3-4:8-10:2-4 for the composite ethanol solution of tetraethyl orthosilicate and 1-tetradecene:ethanol solution of boric acid:composite aqueous solution of hexadecyltrimethylammonium bromide and triethylamine: aqueous ammonia, wherein the mass percentage of the solute in the aqueous ammonia is 10%.
4. The method for preparing a heat-resistant fine enameled round copper wire according to claim 1, characterized in that: In the step (2), the volume ratio of γ-glycidyloxypropyltrimethoxysilane added to the ethanol aqueous solution is γ-glycidyloxypropyltrimethoxysilane:ethanol aqueous solution = 1:80-100, wherein the volume percentage of ethanol in the ethanol aqueous solution is 85%-90%; the mass ratio of the doping powder added to the solution is doping powder:solution = 1:50-100.
5. The method for preparing a heat-resistant fine enameled round copper wire according to claim 1, characterized in that: In the step (2), the concentration of N-(4-hydroxyphenyl)maleimide in the ethanol solution of N-(4-hydroxyphenyl)maleimide is 0.6-0.9 g / 100 mL, and the solvent is ethanol; the dried powder and triphenylphosphine are added to the ethanol solution of N-(4-hydroxyphenyl)maleimide in a ratio of dried powder:triphenylphosphine:ethanol solution of N-(4-hydroxyphenyl)maleimide=1-3 g:0.2-0.3 g:100 mL.
6. The method for preparing a heat-resistant fine enameled round copper wire according to claim 1, characterized in that: In the step (3), the mass ratio of the cerium acetate, 2-ethyl-4-methylimidazole and dichloromethane is cerium acetate: 2-ethyl-4-methylimidazole: dichloromethane = 1.3-1.8: 1.2-1.6: 100; the mass ratio of the modified powder added to the mixture is mixture: modified powder = 50:
1.
7. The method for preparing a heat-resistant fine enameled round copper wire according to claim 1, characterized in that: In the step (4), the mass ratio of the filler powder added to xylene is filler powder:xylene=1:15-20; the mass percentage of the filler powder in the paint solution is 10%-12%.